FEATURES OF FORMATIVE SUFFIXES OF THE MODERN RUSSIAN LANGUAGE (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
In the article, the author examines the forms of word formation of the modern Russian language by affixation. In the course of the study, it was shown that the most productive means of affixation are the following: suffixation, prefix, null suffixation and affix-like word formation, and suffixation is the most applicable. The results of this study can contribute to the development of lexical derivation problems.